2012
DOI: 10.1017/s1368980012000973
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast consumption and CVD risk factors in European adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study

Abstract: AbstractObjectiveTo examine the association between breakfast consumption and CVD risk factors in European adolescents.DesignCross-sectional. Breakfast consumption was assessed by the statement ‘I often skip breakfast’ and categorized into ‘consumer’, ‘occasional consumer’ and ‘skipper’. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
91
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 55 publications
16
91
2
2
Order By: Relevance
“…There are only a few studies that approach the factors associated with skipping breakfast. In general, they report a positive association between breakfasting and healthy lifestyles, such as not smoking, being physically active, controlling body weight and avoiding alcoholic beverages 3,6,7,10,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few studies that approach the factors associated with skipping breakfast. In general, they report a positive association between breakfasting and healthy lifestyles, such as not smoking, being physically active, controlling body weight and avoiding alcoholic beverages 3,6,7,10,24 .…”
Section: Discussionmentioning
confidence: 99%
“…This meal has also been associated with less visceral fat and higher percentage of lean mass 9,24 . It is known that reduction of body weight and fat percentage is important for the prevention and control of diseases, especially cardiovascular diseases and glucose intolerance, and, consequently, diabetes Mellitus 9,24,26 . Corroborating these findings, Pereira et al 10 observed better blood glucose control in people who breakfasted frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents and children are still dependants and they need adequate attention and care in order for them to be able to develop meals and food habits that are healthy and will promote good nutritional status (Lazzeri et al, 2013;Nanney et al, 2011;Storey et al, 2011;Wate et al, 2013). Skipping breakfast and unhealthy food consumption may lead to micro nutrients deficiencies and poor nutritional status (Acham et al, 2012;Hallstrom et al, 2013;Pereira et al, 2011;So et al, 2011). The consequences of poor nutritional status at the early stage of life may be so serious that it can result in depression, lack of self esteem, unconsciousness, anxiety, poor cognition and academic achievements and in extreme condition a premature death among school children and used to measure height and weight of participants two adolescents (Acham et al, 2012;Arora et al, 2012; times each and mean height and weight were Bhurtun and Jeewon, 2013;Hoyland et al, 2012;Matthys determined.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the prevalent o f and ethical considerations were dully observed. diseases such as diabetes, elevated blood pressure, stroke, overweight and obesity, respiratory and cardiovascular diseases has been positively associated to unhealthy dietary consumption emanating from food transition (Briefel et al, 2009;Gupta et al, 2012;Hallstrom et al, 2013;Kral et al, 2011;Rampersaud et al, 2005), this has contributed to poor health care delivery in developing countries. Majority of countries in Africa, Middle East and Asia continents have a larger proportion of population that is less than 40 years (Baldwin and Amati, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, regular breakfast consumption has been associated with a healthier cardiovascular profile in European adolescents (5) . Breakfast has been documented to make an essential contribution to nutrient intakes (1,7,8) , due to its contribution of approximately 20 % to total daily energy intake and content of specific nutrients such as vitamins (9) .…”
mentioning
confidence: 99%